Role of metabolism, resistance, and/or antagonism as drivers of endomicrobiomes assemblage in Origanum heracleoticum L - Giulia Semenzato; Francesco Vitali; Arcangela Frascella; Ludovica Lollini; Stefano Mocali; Alessio Papini; Renato Fani; Giovanni Emiliani (Communications Biology)
Abstract The understanding of selective forces driving the compartmentalization of microbiota in plants remains limited. In this study, we performed a phenotypic characterization of bacterial endophytes isolated from the medicinal plant Origanum heracleoticum, together with the determination of the antibiotic resistance profiles and the antagonistic interactions of communities within and across different plant organs. Results revealed organ-related differences in the metabolic capabilities of bacteria, with those associated with stems displaying the highest metabolic activity for carbon sources. Contrarily, the patterns of antibiotic resistance appeared closely aligned with the taxonomical classification of the endophytes. The presence of antagonistic interactions, likely spurred by resource limitations, favor bacteria exhibiting greater metabolic plasticity. In conclusion, this research advances our comprehension of the intricate dynamics between plants and their associated microbiota, indicating that its composition is mainly influenced by forces contributing to the selection of distinct functions and phenotypic traits.